2011
DOI: 10.1097/rlu.0b013e31820aa1a1
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FLT PET: A Noninvasive Diagnostic Tool for Visualization of the Bone Marrow Compartment in Patients With Aplastic Anemia

Abstract: This pilot study demonstrates that F-18 FLT scan provides a highly distinctive overview of the bone marrow compartment in AA that might be helpful for making a proper diagnosis and monitoring treatment response of AA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…However, 18 F-FLT PET also has been used to measure the health and proliferation of the marrow, especially in patients undergoing bone marrow transplantation (12). 18 F-FLT PET imaging was found useful in evaluating bone marrow in patients with aplastic anemia (13). Interestingly, the main characteristic of 18 F-FLT PET in patients with extramedullary hematopoiesis was higher uptake in the spleen and liver (14).…”
Section: Bone Marrow and Hematologic Malignanciesmentioning
confidence: 99%
“…However, 18 F-FLT PET also has been used to measure the health and proliferation of the marrow, especially in patients undergoing bone marrow transplantation (12). 18 F-FLT PET imaging was found useful in evaluating bone marrow in patients with aplastic anemia (13). Interestingly, the main characteristic of 18 F-FLT PET in patients with extramedullary hematopoiesis was higher uptake in the spleen and liver (14).…”
Section: Bone Marrow and Hematologic Malignanciesmentioning
confidence: 99%
“…Agool et al studied a group of 18 patients with different hematologic disorders, among which were two patients with MM. The authors found that the affected osteolytic areas in these two MM patients demonstrated a low 18 F-FLT uptake [56]. In a pilot study on combined 18 F-FDG and 18 F-FLT PET/CT imaging in 8 myeloma patients (4 patients with symptomatic MM, 4 patients with SMM) the number of myeloma-indicative lesions was significantly higher for 18 F-FDG PET/CT than for 18 F-FLT PET/CT.…”
Section: F-fluorothymidine ( 18 F-flt)mentioning
confidence: 93%
“…It has clear contrast advantages over 18F-FDG in the brain and urinary tract owing to the relatively low overall cellular turnover in these organs, but the high normal cellular proliferation in the bone marrow limits its value here (Shields, 2003 ). Its high bone marrow uptake has, in fact, led to its being used to visualize the total distribution of the hematopoietic bone marrow compartment in aplastic anaemia (Agool et al , 2011 ). The same problem in differentiating malignancy from rapidly proliferating normal tissue applies to lymph nodes, where benign reactive hyperplasia is associated with a high proliferative rate, and 18F-FLT has shown poor specifi city (17%) in the detection of nodal metastases (Troost et al , 2007 ).…”
Section: -F Fl Uoro-l-thymidine (Flt)mentioning
confidence: 98%